The Dynamics of Poverty and Social Support: Longitudinal Evidence from Urban Households - Darmin Tuwu (Inovasi Saintific Review, 2026)
This study examines the dynamics of poverty and the role of social support among urban households, with a focus on understanding how welfare conditions evolve over time. The research aims to analyze patterns of chronic and transient poverty, as well as the influence of formal and informal support systems on household resilience. The study is based on a qualitative longitudinal design involving 30 poor urban households selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic analysis to identify key patterns and relationships. The findings reveal that urban poverty is highly dynamic, with households frequently transitioning in and out of poverty due to economic shocks and unstable livelihoods. Social support plays a crucial role as both a coping mechanism and a protective factor; however, its effectiveness is constrained by weak social networks and unequal access to formal assistance. The study also finds that survival strategies adopted by households are often short-term and insufficient to ensure long-term economic stability. This research contributes to the literature by integrating poverty dynamics and social support within a longitudinal qualitative framework, offering a more comprehensive understanding of urban poverty. It also provides important policy insights for strengthening inclusive and sustainable social protection systems.